Fetal genetic findings by chromosomal microarray analysis and karyotyping for fetal growth restriction without structural malformations at a territory referral center: 10-year experience - Xiaoqing Wu; Shuqiong He; Ying Li; Danhua Guo; Xuemei Chen; Bin Liang; Meiying Wang; Hailong Huang; Liangpu Xu (BMC, 2023)
Abstract Background Prenatal invasive genetic testing is commonly recommended to pregnancies of early-onset FGR or FGR combined with a structural defect. Our study aimed to explore the genetic findings for FGR without structural malformations according to cytogenetic karyotyping and single nucleotide polymorphism array (SNP array) technology over a 10-year period. Methods A total of 488 pregnancies diagnosed with FGR without structural malformation were retrospectively reviewed. Cytogenetic karyotyping was performed on all the subjects, and SNP array was available from 272 of them. Based on the gestational age at onset, the cohort was classified into four groups: ≤ 24, 25-28, 29-32, and > 32 weeks of gestation. According to the ultrasound findings, they were grouped into isolated FGR, FGR with soft markers, and FGR with non-structural anomalies. In pregnancies of young maternal age, based on the results of maternal serum screening (MSS), they were categorized into high-risk and low-risk MSS groups. Results Nineteen (3.9%) cases of chromosomal abnormalities were detected by cytogenetic karyotyping, including 11 cases of numerical abnormalities, 5 cases of structural abnormalities, and 3 cases of mosaicism. Trisomy 21 was the most frequent abnormality. Abnormal karyotypes were more frequently observed in cases diagnosed at ≤ 24 weeks (7.2%) than those in any other group. Among pregnancies with normal karyotype, an incremental yield of 4.2% were revealed by SNP array technology regarding clinically relevant aberrations. The additional detection rates by SNP array in cases diagnosed at ≤ 24 weeks (6.5%), cases with soft markers (9.5%), and cases with high-risk MSS (12.0%) were higher than those in other groups within each classification. All the cases with abnormal karyotypes and 7 out of 11 pregnancies with clinically relevant anomalies revealed by SNP array alone resulted in pregnancy terminations. Conclusion Chromosome abnormality is an important etiology for FGR with no associated structural malformations, and plays a crucial role in pregnancies decision-making. SNP array improves the detection of genetic anomalies especially in FGR diagnosed at ≤ 24 weeks, FGR combined with soft makers, and FGR combined with high-risk MSS.